Immune priming: the secret weapon of the insect world - Gerard Sheehan (Taylor & Francis Group, 2020)
Insects are a highly successful group of animals that inhabit almost every habitat and environment on Earth. Part of their success is due to a rapid and highly effective immune response that identifies, inactivates, and eliminates pathogens. Insects possess an immune system that shows many similarities to the innate immune system of vertebrates, but they do not possess an equivalent system to the antibody-mediated adaptive immune response of vertebrates. However, some insect do display a process known as immune priming in which prior exposure to a sublethal dose of a pathogen, or pathogen-derived material, leads to an elevation in the immune response rendering the insect resistant to a subsequent lethal infection a short time later. This process is mediated by an increase in the density of circulating hemocytes and increased production of antimicrobial peptides. Immune priming is an important survival strategy for certain insects while other insects that do not show this response may have colony-level behaviors that may serve to limit the success of pathogens. Insects are now widely used as in vivo models for studying microbial pathogens of humans and for assessing the in vivo efficacy of antimicrobial agents. Knowledge of the process of immune priming in insects is essential in these applications as it may operate and augment the perceived in vivo antimicrobial activity of novel compounds. Abbreviations: 1,3-dibenzyl-4,5-diphenyl-imidazol-2-ylidene silver(I) acetate; SBC3: antimicrobial peptides; AMPs: dorsal-related immunity factor; DIF: Down syndrome cell adhesion molecule; Dscam: Lipopolysaccharide; LPS: Pathogen-associated molecular patterns; PAMPS: Patterns recognition receptors; PRR: Prophenoloxidase; PO: Toll-like receptors; TLRs: Toll/IL-1R; TIR, Transgenerational Immune Priming; TgIP: Tumor necrosis factor-α; TNF-α.